Dinamika Dukungan dan Penolakan Masyarakat Terhadap Gaya Berpakaian Remaja di Desa Datahu, Kecamatan Tibawa - Harold, Rudy; Tamu, Yowan; Latare, Sainudin; Kasim, Yulian (Sosiologi Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Clothing is a basic human necessity that is intertwined with socio-cultural conditions, ethical considerations, aesthetics, and individual expressions of belief. The relationship between clothing and fashion has always been close, especially in the present era where various clothing designs exist, ranging from very loose to very tight and from modest to revealing. The purpose of this research is to understand the perspective of the community in the village of Datahu, Tibawa Subdistrict, towards teenagers who choose to dress provocatively. The ethnographic investigation method is employed, aiming to depict and examine cultural groups to identify evolving patterns of language, behavior, and beliefs. Documentation, interviews, and observations are utilized to collect data. The research findings indicate that: First, teenage girls who tend to dress provocatively appear to form a supportive community and remain optimistic. They strive to stay authentic, maintaining what they like. Second, the majority of women in the Datahu village follow current teenage fashion trends due to the changing times and societal influence. Many teenage girls in Datahu adopt a glamorous lifestyle with celebrity-like appearances and Western-style revealing clothing, ultimately violating ethical dressing norms according to religious standards. Third, regarding the community's perspective on women who choose to dress provocatively, there are both supporters (pro) and dissenters (contra), depending on individual viewpoints. However, the majority of the Datahu village community tends to disagree with the use of revealing clothing.